FRI0340 Birth Outcomes Among Infants of Women with Chronic Inflammatory Arthritis or Psoriasis Treated and not Treated with Etanercept (Enbrel) During Pregnancy. (9th June 2015) - Accortt, N.; Carman, W.J.; Enger, C.; Iles, J.; Anthony, M.S.
Abstract : Background: Limited population-based data are available regarding the safety of etanercept (ETN) use during pregnancy. Objectives: The purpose of this study was to describe the prevalence of birth outcomes among women with chronic inflammatory arthritis (cIA) or psoriasis (PsO) with or without ETN exposure during pregnancy and among a non-disease, non-ETN control group. Methods: Using administrative data from 1995 through June 2012, we identified infants of women with cIA (defined using ICD-9 codes as rheumatoid arthritis, psoriatic arthritis, juvenile idiopathic arthritis, and ankylosing spondylitis) or PsO, treated with ETN or not treated with any tumor necrosis factor inhibitor (TNFi) during pregnancy. A general population control group without cIA or PsO or TNFi treatment during pregnancy was frequency matched to the ETN cIA and PsO groups for age and year of pregnancy. The prevalence of birth outcomes (major congenital malformations (MCM), preterm birth and low birth weight (LBW)) was calculated among linked infants in the 6 cohorts. ICD9 codes were used to identify outcomes. For MCM claims, medical charts were abstracted to verify the outcome. As medical charts were available for less than half of the identified infants, we further developed body-system specific algorithms from existing medical charts and applied them to all MCM claims to identify MCMs with greater specificity. Prevalence of LBW and preterm birth are based on claims information only. Results: We identified 3, 523 live births, of which 3, 238 were linkable to mothers and available for assessment of birth outcomes. Prevalence of LBW was higher among the etanercept exposed cIA and PsO cohorts compared with the unexposed disease cohorts and general population (Table ). Preterm birth was similar among the cIA cohorts (exposed and unexposed) but higher than the general population. There were 546 infants with ≥ one claim for a MCM, of which 152 charts were procured. From these charts, 55 (36.2%) were confirmed as MCM. Application of the chart-derived algorithms increased the confirmation rate to 80.4%. The chart-based and algorithm-based prevalence of malformations were comparable across all cohorts. Conclusions: The proportion of infants with major congenital malformations was similar across cohorts. The prevalence of LBW and preterm birth was higher among women with arthritis as compared to matched controls, but was similar among the cIA cohorts. Acknowledgements: Study funded by Immunex, a wholly owned subsidiary of Amgen Inc. and through a research contract between Amgen, Inc. and Optum, Epidemiology Disclosure of Interest: N. Accortt Shareholder of: Amgen, Employee of: Amgen, W. Carman Shareholder of: United Health Group, Employee of: Optum, C. Enger Shareholder of: United Health Group, Employee of: Optum, J. Iles Shareholder of: Amgen, Employee of: Amgen, M. Anthony Shareholder of: Amgen